Determination of critical swimming velocity for long distance swimmer and sprint swimmer - Funai, Y.; Kitagawa, K. (Japanese Journal of Sciences in Swimming and Water Exercise, 2014)
The purpose of this study was to find out the physiological response difference of long-distance (LDS) and sprint swimmers (SPS) to intermittent swimming test at critical swimming velocity (CV) in swimming flume. First, twelve trained swimmers (LDS, n=6; SPS, n=6) swam at five swimming speeds with maximal effort to determine the CV. Then, ventilation (VE), oxygen consumption (VO2), heart rate (HR), blood lactate concentration (BLa), respiratory exchange ratio (R) and relative oxygen consumption (%VO2max) were examined during intermittent swimming test at CV. For the LDS, only HR increased significantly during intermittent swimming test. For the SPS, significant increases in VE, VO2, HR, and %VO2max were observed. In the comparison between the two groups, VE, VO2, HR, BLa and R were significantly higher in the LDS at all repetitions. Thus, intermittent swimming at CV induces constant physiological intensity in the LDS and gradually increases physiological intensity in the SPS, and there were clear differences in physiological responses between LDS and SPS.